AN ANALYSIS OF GRAMMATICAL COHESION OF REFERENCE IN A SHORT STORY ENTITLED "THE PRINCESS AND THE PEA" - Astri Afriliani; Sri Supiah Cahyati (PROJECT (Professional Journal of English Education), 2022)
This study aims to analyze the type of Grammatical Cohesion using Halliday and Hasan (1976) theory. This research applied Descriptive qualitative method, while  the data were taken from "The Princess and The Pea" short story text. This research is carried out by reading the whole text, finding and collecting the references used in it, then analyzing the number of references identified and categorizing them into three types: Personal, Demonsrative, and Comparative references. The results show that there are a Grammatical Cohesion used. From the data that have been analyzed, there were one Comparative reference and it shows that there are 33 Personal references and the most Grammatical Cohesion of reference found in the data was Demonstrative reference in amount 42 references. From the findings, it can be concluded that Demonstrative reference ‘the’is the mostly used by the writer to refer a particular thing in the story. It means that in a fiction short story the use of Demonstrative reference as part of Grammatical Cohesion is required to presuming a definite meaning. Keywords:  Grammatical Cohesion, Reference